2019
DOI: 10.3389/fnins.2019.00746
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography and Functional Magnetic Resonance Imaging-Guided Simultaneous Transcranial Direct Current Stimulation and Repetitive Transcranial Magnetic Stimulation in a Patient With Minimally Conscious State

Abstract: Objective A minimally conscious state (MCS) is characterized by discernible behavioral evidence of consciousness that cannot be reproduced consistently. This condition is highly challenging to treat. Recent studies have demonstrated the potential therapeutic effect of non-invasive brain stimulation in patients with MCS. In one patient in an MCS, we delivered simultaneous transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS) based on an individual br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…Although it is difficult to assess which patients are most likely to respond to TMS given the heterogeneity of treatment protocols and patient characteristics, it is important to note that TMS was performed without any reported adverse effects. From the 10 included studies, 8 discussed the safety of the TMS interventions utilized and explicitly reported that no patients experienced adverse effects (24,31,32,(34)(35)(36)(37)(38). The other two studies did not report any adverse effects, although no formal statement concerning safety of TMS was included in either (30,33).…”
Section: Proposing a Tms Protocol For Doc Patientsmentioning
confidence: 99%
“…Although it is difficult to assess which patients are most likely to respond to TMS given the heterogeneity of treatment protocols and patient characteristics, it is important to note that TMS was performed without any reported adverse effects. From the 10 included studies, 8 discussed the safety of the TMS interventions utilized and explicitly reported that no patients experienced adverse effects (24,31,32,(34)(35)(36)(37)(38). The other two studies did not report any adverse effects, although no formal statement concerning safety of TMS was included in either (30,33).…”
Section: Proposing a Tms Protocol For Doc Patientsmentioning
confidence: 99%
“…Of the 16 patients who completed the treatment, four showed improvements on the first day of treatment, while another five gained improvements following subsequent treatments, with a significant therapeutic effect at 7 days following the end of the stimulation, [ 71 ] thus suggesting that tDCS may have accumulative and long-lasting effects. A number of other studies followed the one that involved the delivering of direct current stimulation to the DLPFC, [ 72 82 ] inferior/posterior parietal cortex, [ 83 87 ] and the M1. [ 88 91 ] Most of the studies reached a similar conclusion that tDCS can improve the consciousness of some patients with DOCs, and its therapeutic efficacy among patients with MCS is especially significant.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that consciousness is regulated by the activation of neural pathways. Connectivity is an important feature of neural pathways [20], and the disruption of pathway connectivity is related to the degree of consciousness breakdown [13], with a significant relationship to prognosis [21]. Recent findings have suggested that the response to rTMS in DOC patients is mediated by the neural networks preserved after insult [22].…”
Section: Introductionmentioning
confidence: 99%
“…The induced effects of rTMS depend, in part, on the parameters of stimulation used. As such stimulation at high frequencies (>5 Hz) can induce neural excitation, the frequency commonly utilized in previous studies ranged from 5 to 20 Hz [21,31,38]. Moreover, repetitive TMS may induce more significant perturbations in contrast to single TMS, with deep and sustained effects on subcortical regions [49] that can be maintained long after completing rTMS sessions [36].…”
mentioning
confidence: 99%